Friction material and preparation method thereof

By using a combination of load fibers and pore adjustment fibers, the problems of flatness and stability caused by unstable friction performance in the thickness direction and filler caused by fillers are solved, and more stable friction performance and improved material performance are achieved.

CN119755225APending Publication Date: 2025-04-04SHANGHAI CARBON POWER NEW ENERGY TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411973558.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The friction performance of wet paper-based friction materials is unstable in the thickness direction, and the filler blocks the mesh holes and residual fillers in the white water lead to poor paper flatness and poor batch stability.

Method used

Load fibers and pore adjustment fibers are used, which include fiber matrix and fillers loaded on the fiber matrix. The density difference is less than the preset value. Friction materials are prepared by decomposition, immersion of binders and hot pressing curing treatment.

Benefits of technology

The uniform adhesion of fibers and fillers is achieved, and the problem of fillers blocking the mesh holes and residual fillers in white water is avoided. The friction performance stability of the thickness direction of the friction material is improved, and the heat resistance, friction coefficient and compression elasticity of the material are adjusted.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119755225A_ABST
    Figure CN119755225A_ABST
Patent Text Reader

Abstract

The invention provides a friction material and a preparation method thereof, relates to the technical field of mechanical brake transmission, and aims to solve the problem that the friction performance of the friction material is unstable in the thickness direction. The friction material comprises at least one loading fiber, at least one pore adjusting fiber and a binder, each loading fiber comprises a fiber matrix and a filler loaded on the fiber matrix, and the density difference of every two loading fibers is smaller than a preset density difference. The preparation method of the friction material comprises the friction material provided by the technical scheme. The preparation method of the friction material is used for preparing the friction material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of mechanical brake transmission, and in particular to a friction material and a preparation method thereof. Background Art

[0002] Wet paper-based friction material is a friction material that works in oil and is widely used in wet brake and torque transmission devices of cars, heavy vehicles and engineering machinery. Wet paper-based friction materials are generally prepared and formed using papermaking technology, that is, using fibers and fillers as raw materials for processing and forming. However, due to the wide variety of fibers and fillers used in wet paper-based friction materials and the large density differences, it is easy to cause the friction performance of the prepared wet paper-based friction materials to be unstable in the thickness direction. Summary of the invention

[0003] The object of the present disclosure is to provide a friction material and a preparation method thereof, which are used for preparing the friction material.

[0004] In order to achieve the above-mentioned objectives, the present disclosure provides the following technical solutions: a friction material, comprising: at least one load fiber, at least one pore regulating fiber and a binder, each of the load fibers comprising a fiber matrix and a filler loaded on the fiber matrix, and the density difference between every two of the load fibers is less than a preset density difference.

[0005] Compared with the prior art, in the friction material provided by the present disclosure, by using loaded fibers, each loaded fiber includes a fiber matrix and a filler loaded on the fiber matrix, so that the fiber and the filler can be uniformly adhered together to form loaded fibers for mixing with other raw materials, without further adding fillers, thereby avoiding the occurrence of problems such as poor paper flatness caused by fillers blocking mesh holes and poor batch stability caused by residual fillers in white water. At the same time, since the density difference between each two loaded fibers is less than the preset density difference, it can be seen that after mixing and adsorbing the fiber and the filler in a certain ratio, the density difference between the obtained loaded fibers is small, thereby solving the problem of unstable friction performance in the thickness direction caused by the poor density difference between the fiber and the filler.

[0006] Based on this, pore-adjusting fibers are added to the friction material to adjust the pore size of the friction material, thereby adjusting the heat resistance, friction coefficient and compression resilience of the material.

[0007] The present disclosure also provides a method for preparing a friction material, the method for preparing the friction material comprising:

[0008] The load fibers and the pore-adjusting fibers are loosened and paper-made to obtain base paper;

[0009] immersing the base paper in a binder to obtain a pre-cured base paper;

[0010] The pre-cured base paper is subjected to a heat-pressing curing process to obtain a friction material.

[0011] Compared with the prior art, the beneficial effects of the method for preparing the friction material provided in the present disclosure are the same as the beneficial effects of the friction material described in the above technical solution, which will not be described in detail here. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] The drawings described herein are used to provide a further understanding of the present disclosure and constitute a part of the present disclosure. The illustrative embodiments of the present disclosure and their descriptions are used to explain the present disclosure and do not constitute an improper limitation on the present disclosure. In the drawings:

[0013] Figure 1 The flowchart of the method for preparing the friction material provided by the exemplary embodiment of the present disclosure is shown. Figure 1 ;

[0014] Figure 2 The flowchart of the method for preparing the friction material provided by the exemplary embodiment of the present disclosure is shown. Figure 2 . DETAILED DESCRIPTION

[0015] Hereinafter, embodiments of the present disclosure will be described with reference to the accompanying drawings. However, it should be understood that these descriptions are exemplary only and are not intended to limit the scope of the present disclosure. In addition, in the following description, descriptions of well-known structures and technologies are omitted to avoid unnecessary confusion of the concepts of the present disclosure.

[0016] Wet paper-based friction material is a kind of friction material working in oil, which is widely used in wet brake and torque transmission devices of cars, heavy vehicles and engineering machinery. It has the characteristics of moderate friction coefficient, dynamic / static friction coefficient close to 1, small change of dynamic friction coefficient with linear speed, low noise, etc. Wet paper-based friction material is generally prepared by papermaking process, that is, raw materials such as fiber and friction performance regulating filler are made into paper, impregnated with resin binder, cut and heated to solidify.

[0017] The inventors found that due to the large variety of fibers and friction performance adjusting fillers in the wet paper-based friction material and the large density differences, it is easy for the high-density fillers to settle at the bottom, resulting in instability of the material's performance in the thickness direction during use.

[0018] In addition, pore structure is an important factor affecting the thermal, mechanical and friction properties of wet paper-based friction materials. During the papermaking process, the disordered arrangement of fibers and fillers will cause some through holes to be blocked by fillers, making the pore structure difficult to control.

[0019] After papermaking, some fillers will remain on the papermaking mesh and need to be cleaned on time, otherwise the subsequent processed paper will have poor flatness. The fillers will clog the mesh holes, and there are a lot of fillers in the white water of papermaking. Direct reuse of the white water can easily cause filler accumulation in the white water and poor batch stability of paper. The recycling of the white water after treatment requires sedimentation, filtration, centrifugal separation, etc., which requires high equipment investment and high energy consumption. Failure to reuse the white water will result in high water consumption.

[0020] In order to overcome the above problems, an exemplary embodiment of the present disclosure provides a friction material, comprising: at least one load fiber, at least one pore adjustment fiber and a binder, each load fiber comprising a fiber matrix and a filler loaded on the fiber matrix, and the density difference between each two load fibers is less than the preset density difference. It should be understood that the number of load fibers and the number of pore adjustment fibers in the friction material provided by the present disclosure can be selected according to the actual application scenario, and are not limited here. The binder here can include melamine or cashew nut shell oil or silicone modified phenolic resin solution, etc., but is not limited thereto.

[0021] As can be seen from the above, in the friction material provided by the present disclosure, by using loaded fibers, each loaded fiber includes a fiber matrix and a filler loaded on the fiber matrix, so that the fiber and the filler can be uniformly adhered together to form loaded fibers for mixing with other raw materials, and no filler is added, thereby avoiding the occurrence of problems such as poor paper flatness caused by filler blocking the mesh and poor batch stability caused by residual filler in white water. At the same time, since the density difference between each two loaded fibers is less than the preset density difference, it can be seen that after mixing and adsorbing the fiber and the filler in a certain ratio, the density difference between the obtained loaded fibers is small, thereby solving the problem of unstable friction performance in the thickness direction caused by the poor density difference between the fiber and the filler.

[0022] Based on this, pore-adjusting fibers are added to the friction material to adjust the pore size of the friction material, thereby adjusting the heat resistance, friction coefficient and compression resilience of the material.

[0023] As a possible implementation, the mass ratio of the load fiber and the pore adjustment fiber is (40-100): (31-65). For example, the mass ratio of the load fiber and the pore adjustment fiber can be 40:31, 55:55, and 100:65, etc., but is not limited thereto. By adding load fibers and pore adjustment fibers that meet the above mass ratio requirements, the pore structure of the friction material can be adjusted, so that the pore structure of the prepared friction material can be controlled, thereby improving the stability between different batches, improving the service life and wear resistance.

[0024] As a possible implementation, the plurality of loaded fibers may include cellulose fibers loaded with calcium sulfate whiskers, first density filler fibers, and second density filler fibers.

[0025] In some optional embodiments, when the above-mentioned loaded fibers include cellulose fibers loaded with calcium sulfate whiskers, first density filler fibers, and second density filler fibers, the mass ratio of cellulose fibers loaded with calcium sulfate whiskers, first density filler fibers, and second density filler fibers is (20-40): (10-30): (10-30). For example, the mass ratio of cellulose fibers loaded with calcium sulfate whiskers, first density filler fibers, and second density filler fibers can be 20:10:10, 30:25:25, and 40:30:30, etc., but not limited thereto, so as to adjust the voids of the friction material and ensure that the friction material prepared has good wear resistance.

[0026] In some optional modes, the cellulose fiber loaded with calcium sulfate whiskers comprises calcium sulfate dihydrate aqueous solution and cellulose fiber, and the concentration of calcium sulfate dihydrate aqueous solution is 5%-10%. For example, the concentration of calcium sulfate dihydrate aqueous solution can be 5%, 7% and 10%, etc., but is not limited thereto. By limiting the concentration of calcium sulfate dihydrate aqueous solution, while ensuring that the cellulose fiber surface is loaded with enough fillers, the situation of reducing the fiber surface strength caused by the excessively high concentration of calcium sulfate dihydrate is avoided.

[0027] In some optional modes, the mass ratio of calcium sulfate dihydrate and cellulose fiber in the above-mentioned calcium sulfate dihydrate aqueous solution is 1:1, and cellulose fiber can be one or more of cotton fiber, hemp fiber and wood fiber, for example, cellulose fiber can be cotton fiber, hemp fiber, wood fiber and cotton fiber, hemp fiber and wood fiber, etc., and is not limited to this. Since cellulose fibers are all hydrophilic fibers, they have good wettability in calcium sulfate dihydrate aqueous solution, which is conducive to the in-situ growth of calcium sulfate whiskers. At the same time, by configuring the calcium sulfate dihydrate aqueous solution that meets the above-mentioned concentration requirements, so that calcium sulfate dihydrate dissolves in water to reach supersaturation, supersaturated dihydrate and calcium sulfate nucleate in a large amount in the solution under the auxiliary action of the regulator, under hydrothermal conditions, calcium sulfate dihydrate is converted into calcium sulfate hemihydrate whiskers loaded on cellulose fibers, forming cellulose fibers loaded with calcium sulfate whiskers.

[0028] In some optional embodiments, the first density filler fiber includes a first density filler and a core-skin fiber, and the second density filler fiber includes a second density filler and a high-performance fiber, and the density of the first density filler is greater than that of the second density filler. Since the core-skin fiber has a relatively low density, while the high-performance fiber has a relatively high density, the first density filler with a high density is added to the core-skin fiber with a relatively low density, and the second density filler with a relatively low density is added to the high-performance fiber with a relatively high density, so that the density difference between the first density fiber and the second density fiber finally prepared is less than the preset density difference, the density difference between the filler and the fiber is adjusted, and the filler distribution in the thickness direction of the friction material can be uniform during the papermaking process, thereby improving the friction performance and stability of the friction material. It should be understood that the preset density difference involved in the exemplary embodiment of the present disclosure can be determined based on the selection of actual raw materials, and is not limited here.

[0029] In some optional embodiments, the mass ratio of the first density filler and the core-skin fiber is (2-5):1. For example, the mass ratio of the first density filler and the core-skin fiber can be 2:1, 3:1, 5:1, etc., but is not limited thereto. The mass ratio of the second density filler and the high-performance fiber is (0.5-5):1. For example, the mass ratio of the second density filler and the high-performance fiber can be 0.5:1, 2:1, 5:1, etc., but is not limited thereto. By adding fibers and fillers that meet the above-mentioned mass ratio requirements, the pore structure and density of the prepared first density filler fibers and second density filler fibers can be controlled, so that the filler adhered to the fiber surface is more evenly distributed, thereby improving the stability of the fibers finally prepared, solving the problems of mesh pollution and water pollution caused by the addition of fillers in the papermaking process, and ensuring the performance of the prepared friction material.

[0030] In some optional embodiments, the first density filler includes a density greater than 1.2 g / cm 3 The core-sheath fiber includes one or both of a core-sheath fiber with polypropylene as the core layer and a core-sheath fiber with polyester as the core layer. For example, the core-sheath fiber can be a core-sheath fiber with polypropylene as the core layer, a core-sheath fiber with polyester as the core layer, or a mixture of a core-sheath fiber with polypropylene as the core layer and a core-sheath fiber with polyester as the core layer. By selecting the core-sheath fiber, it can be ensured that the outer skin of the core-sheath fiber can be in a slightly molten state under appropriate temperature conditions and has viscosity, so that the first density filler can be adhered to the surface of the core-sheath fiber to form a first density filler fiber.

[0031] In some optional embodiments, the first density filler includes one or more of barium sulfate, metal powder, graphite, aluminum oxide, and magnesium oxide. For example, the first density filler may include barium sulfate, metal powder, graphite, aluminum oxide, magnesium oxide, and barium sulfate, metal powder, graphite, aluminum oxide, and magnesium oxide, etc., but is not limited thereto. It should be understood that the selection of the first density filler can be determined according to the application scenario of the friction material. Different application scenarios have different performance requirements for the friction material and require different fillers, which are not limited here.

[0032] In some optional embodiments, the second density filler includes a density less than 1.2 g / cm 3 The high-performance fiber includes one or more of aramid fiber, ceramic fiber and carbon fiber. For example, the high-performance fiber may include aramid fiber, ceramic fiber, carbon fiber, aramid fiber, ceramic fiber and carbon fiber, etc., but is not limited thereto. By selecting the above high-performance fiber, it can be ensured that the high-performance fiber can be in a slightly molten state under appropriate temperature conditions and has viscosity, and the second density filler can be adhered to the surface of the high-performance fiber to form a second density filler fiber.

[0033] In some optional embodiments, the second density filler includes one or more of diatomaceous earth, nitrile rubber powder and phenolic resin powder. For example, the second density filler may include diatomaceous earth, nitrile rubber powder, phenolic resin powder, and diatomaceous earth, nitrile rubber powder and phenolic resin powder, etc., but is not limited thereto. It should be understood that the selection of the second density filler can be determined according to the application scenario of the friction material. Different application scenarios have different performance requirements for the friction material and require different fillers, which are not limited here.

[0034] As a possible implementation method, in order to further improve the service life and wear resistance of the friction material, a suitable pore adjustment fiber can be selected according to the composition of the load fiber to adjust the pores of the friction material. The pore adjustment fiber includes one or more of carbon fiber, polyimide fiber, mineral fiber and glass fiber. For example, the pore adjustment fiber can be carbon fiber, polyimide fiber, mineral fiber, glass fiber or carbon fiber, polyimide fiber, mineral fiber and glass fiber, etc., but is not limited thereto.

[0035] The present disclosure also provides a method for preparing a friction material, which is used for preparing the friction material. Figure 1 The flowchart of the method for preparing the friction material provided by the exemplary embodiment of the present disclosure is shown. Figure 1 .like Figure 1 As shown, the method for preparing the friction material includes:

[0036] Step 110: deflaking the load fiber and the pore-adjusting fiber to obtain base paper. For example, the load fiber and the pore-adjusting fiber may be configured in a mass ratio of (40-100): (31-65), deflaked in a deflaker, and then formed in a papermaking device after deflaking, and dried to obtain base paper. The drying temperature may be 100°C.

[0037] Step 120: Immerse the base paper in the binder to obtain pre-cured base paper. For example, the dried base paper can be immersed in the binder to make the paper glue content 20%-40%. After the impregnation is completed, pre-curing is performed at 60°C-100°C to obtain a cured base paper. The binder can be melamine, cashew nut shell oil or silicone-modified phenolic resin solution.

[0038] Step 130: The pre-cured base paper is subjected to heat pressing and curing treatment to obtain the friction material. For example, the pre-cured base paper can be subjected to heat pressing at a temperature of 170°C-195°C and a pressure of 1MPa-6MPa to obtain the friction material. The heat pressing temperature here can be 170°C, 185°C, 195°C, etc., but is not limited thereto. The heat pressing pressure can be 1MPa, 5MPa, 6MPa, etc., but is not limited thereto.

[0039] Compared with the prior art, the beneficial effects of the method for preparing the friction material provided in the present disclosure are the same as the beneficial effects of the friction material of the above technical solution, which will not be elaborated here.

[0040] In some alternatives, Figure 2 The flowchart of the method for preparing the friction material provided by the exemplary embodiment of the present disclosure is shown. Figure 2 .like Figure 2 As shown, when the plurality of loaded fibers include cellulose fibers loaded with calcium sulfate whiskers, first density filler fibers, and second density filler fibers, the cellulose fibers loaded with calcium sulfate whiskers include a calcium sulfate dihydrate aqueous solution and cellulose fibers, the concentration of the dihydrate and the calcium sulfate aqueous solution is 5%-10%, the first density filler fibers include a first density filler and a skin-core fiber, the second density filler fibers include a second density filler and a high-performance fiber, and the density of the first density filler is greater than the density of the second density filler, the loaded fibers and the pore-adjusting fibers are debonded and paper-made to obtain a base paper, which may include:

[0041] Step 210: Add the cellulose fiber to the calcium sulfate dihydrate aqueous solution for impregnation to obtain the cellulose fiber pretreated with calcium sulfate whiskers. It should be understood that in order to improve the tightness of the bonding between the cellulose fiber and the gypsum, the cellulose fiber can be added to the dihydrate and calcium sulfate aqueous solution and then impregnated under vacuum negative pressure to ensure that the liquid can fully penetrate into the interior of the cellulose fiber and ensure that the cellulose fiber is in a saturated impregnation state.

[0042] For example, a 5%-10% concentration of dihydrate and calcium sulfate aqueous solution may be prepared first, and then cellulose fibers may be added for vacuum negative pressure impregnation with stirring to make the cellulose fibers account for 5%-10% of the solution by mass.

[0043] Step 220: Under the first reaction condition, the pre-treated cellulose fiber loaded with calcium sulfate whiskers and the conditioning agent are mixed to carry out a crystal growth reaction to obtain the cellulose fiber loaded with calcium sulfate whiskers. The first reaction condition includes a crystal growth reaction time of 100min-150min, for example, the crystal growth reaction time can be 100min, 125min and 150min, etc., but is not limited thereto. The crystal growth temperature is 100℃-150℃, for example, the crystal growth temperature can be 100℃, 125℃ and 150℃, etc., but is not limited thereto. The conditioning agent can be one or both of potassium chloride and sodium chloride, for example, the conditioning agent can be potassium chloride, sodium chloride, and potassium chloride and sodium chloride. The calcium sulfate morphology can be adjusted by adding a conditioning agent to ensure that the performance of the cellulose fiber loaded with calcium sulfate whiskers finally obtained is excellent.

[0044] Exemplary, a conditioning agent can be added to the cellulose fiber of the pre-treatment load calcium sulfate whisker, and the mixture is uniformly reacted in a hydrothermal reactor for 100min-150min. After the reaction is completed, the cellulose fiber of the load calcium sulfate whisker is obtained after water washing and suction filtration. Wherein, the mass ratio of the dihydrate and calcium sulfate, the cellulose fiber and the conditioning agent in the dihydrate and calcium sulfate aqueous solution is (20-100): (20-100): 1, for example, the mass ratio can be 20:20:1, 55:55:1 and 100:100:1, etc., but is not limited thereto. By configuring the cellulose fiber of the load calcium sulfate whisker according to the above-mentioned mass ratio requirement, the whisker uniformity of the cellulose fiber surface of the load calcium sulfate whisker can be improved, thereby improving the overall performance of the cellulose fiber of the load calcium sulfate whisker.

[0045] Step 230: Under the second reaction condition, the first density filler and the core-skin fiber are mixed and heated to obtain the first density filler fiber. The second reaction condition includes a stirring time of 5 min-10 min. For example, the stirring time can be 5 min, 7 min and 10 min, etc., but is not limited thereto. The heating temperature is 105°C-138°C. For example, the heating temperature can be 105°C, 125°C and 138°C, etc., but is not limited thereto. By setting the reaction conditions that meet the above temperature requirements, it can be ensured that the skin layer on the surface of the core-skin fiber is in a slightly molten state, and enough fillers can be adhered, thereby improving the uniformity of the mixing of the fiber and the filler, thereby ensuring that the performance of the prepared first density filler is more stable.

[0046] For example, when the first density filler has a density greater than 1.2 g / cm 3When the core-skin fiber is a core-skin fiber with polypropylene as the core layer, the density is greater than 1.2g / cm 3 The filler is added to the sheath-core fiber with lower density and polypropylene as the core layer, stirred and heated to 105℃-138℃, the stirring time is 5min-10min, and after the stirring is completed, the excess filler is filtered out with a sieve to obtain the first density filler fiber.

[0047] Step 240: Under the third reaction condition, the second density filler and the high-performance fiber are mixed and heated to obtain the second density filler fiber. The third reaction condition includes a stirring time of 5 min-10 min. For example, the stirring time can be 5 min, 7 min and 10 min, etc., but is not limited thereto. The heating temperature is 120°C-140°C. For example, the heating temperature can be 120°C, 135°C and 140°C, etc., but is not limited thereto. By setting the reaction conditions that meet the above temperature requirements, it can be ensured that the surface of the high-performance fiber is in a slightly molten state, and enough fillers can be adhered, thereby improving the uniformity of the mixing of the fiber and the filler, thereby ensuring that the performance of the prepared second density filler is more stable.

[0048] For example, when the second density filler has a density less than 1.2 g / cm 3 When the high-performance fiber is aramid fiber, the density is less than 1.2g / cm 3 The filler is added to the aramid fiber with a higher density, stirred and heated to 120°C-140°C, and the stirring time is 5min-10min. After the stirring is completed, the excess filler is filtered out with a sieve to obtain a second density filler fiber. It should be understood that the mesh number of the sieve involved in the exemplary embodiment of the present disclosure matches the particle size of the filler, and there is no limitation here.

[0049] Step 250: The cellulose fibers loaded with calcium sulfate whiskers, the first density filler fibers, the second density filler fibers, and the pore-adjusting fibers are deflaked and paper-made to obtain base paper. For example, the cellulose fibers loaded with calcium sulfate whiskers, the first density filler fibers, the second density filler fibers, and the pore-adjusting fibers can be deflaked in a deflaker according to a mass ratio of (20-40): (10-30): (10-30): (31-65), and after deflaking, they are formed in a papermaking device and dried to obtain base paper.

[0050] The present disclosure is further described below by way of examples, but the present disclosure is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are selected according to conventional methods and conditions, or according to the product instructions.

[0051] Example 1

[0052] The load fibers used in this embodiment are cellulose fibers loaded with calcium sulfate whiskers, first density filler fibers and second density filler fibers, the pore regulating fibers are carbon fibers, polyimide fibers, mineral fibers and glass fibers, the concentration of the calcium sulfate dihydrate aqueous solution is 5%, the cellulose fibers are cotton fibers, the regulator is potassium chloride, the sheath-core fibers are sheath-core fibers with polypropylene as the core layer, the first density fillers are barium sulfate, graphite and alumina, the second density fillers are diatomaceous earth and phenolic resin powder, the high-performance fibers are aramid fibers, and the binder is a melamine-modified phenolic resin solution.

[0053] Step 1: Preparation of cellulose fibers loaded with calcium sulfate whiskers

[0054] A 5% calcium sulfate dihydrate aqueous solution is prepared, and cotton fibers are added to be impregnated under vacuum and stirred, and potassium chloride is added. After mixing evenly, the mixture is reacted in a hydrothermal reactor for 120 minutes at a heating temperature of 100° C., wherein the mass ratio of calcium sulfate dihydrate, cellulose fibers and potassium chloride in the dihydrate and calcium sulfate aqueous solution is 20:20:1.

[0055] Step 2: Preparation of first density filler fiber

[0056] 20% barium sulfate, 50% graphite and 30% alumina were mixed evenly, added to the core-skin fiber with polypropylene as the core layer, stirred and heated to 105°C for 5 minutes, and the excess filler was filtered out with a sieve after stirring to obtain the first density filler fiber, wherein the mass ratio of the first density filler to the core-skin fiber was 2:1.

[0057] Step 3: Preparation of Second Density Filler Fiber

[0058] Mix 0.4 times diatomaceous earth and 0.1 times phenolic resin powder evenly, add to the high-performance fiber, stir and heat to 120°C, stir for 5 minutes, filter out excess filler with a sieve after stirring, and obtain the second density filler fiber, wherein the mass ratio of the second density filler to the high-performance fiber is 0.5:1.

[0059] Step 4: Preparation of base paper

[0060] 20% of cellulose fiber loaded with calcium sulfate whiskers, 10% of first density filler fiber, 30% of second density filler fiber, 20% of carbon fiber, 2% of polyimide fiber, 10% of mineral fiber, and 8% of glass fiber are configured, and the paper is deflaked in a deflaking machine, and then formed in a papermaking equipment and dried at 100°C. The final basis weight of the paper is 400g / m 2 .

[0061] Step 5: Preparation of pre-cured base paper

[0062] The dried base paper is immersed in a melamine-modified phenolic resin solution to make the glue content of the paper 20%. After the immersion is completed, the base paper is pre-cured at 60°C.

[0063] Step 6: Preparation of Friction Material

[0064] After pre-curing, the paper was hot pressed at 170°C and 1 MPa to obtain the friction material, the properties of which are shown in Table 1.

[0065] Example 2

[0066] The load fibers used in this embodiment are cellulose fibers loaded with calcium sulfate whiskers, first density filler fibers and second density filler fibers, the pore regulating fibers are carbon fibers, polyimide fibers, mineral fibers and glass fibers, the concentration of dihydrate and calcium sulfate aqueous solution is 10%, the cellulose fibers are hemp fibers, the regulator is sodium chloride, the sheath-core fibers are sheath-core fibers with polypropylene as the core layer, the first density fillers are metal powder, graphite, aluminum oxide and magnesium oxide, the second density fillers are diatomaceous earth, nitrile rubber powder and phenolic resin powder, the high-performance fibers are ceramic fibers, and the binder is a phenolic resin solution modified with cashew nut shell oil.

[0067] Step 1: Preparation of cellulose fibers loaded with calcium sulfate whiskers

[0068] A 10% calcium sulfate dihydrate aqueous solution is prepared, and hemp fibers are added to be impregnated with vacuum negative pressure and stirred, and sodium chloride is added. After mixing evenly, the mixture is reacted in a hydrothermal reactor for 100 minutes at a heating temperature of 150° C., wherein the mass ratio of calcium sulfate dihydrate, cellulose fibers and sodium chloride in the calcium sulfate dihydrate aqueous solution is 55:55:1.

[0069] Step 2: Preparation of first density filler fiber

[0070] 5% metal powder, 60% graphite, 20% alumina and 15% magnesium oxide were evenly mixed, added to the core-skin fiber with polypropylene as the core layer, stirred and heated to 138°C for 10 minutes. After stirring, excess filler was filtered out with a sieve to obtain the first density filler fiber, wherein the mass ratio of the first density filler to the core-skin fiber was 5:1.

[0071] Step 3: Preparation of Second Density Filler Fiber

[0072] Mix 4 times of diatomaceous earth, 0.5 times of nitrile rubber powder and 0.5 times of phenolic resin powder evenly, add to the high-performance fiber, stir and heat to 140°C, stir for 10 minutes, filter out excess filler with a sieve after stirring to obtain the second density filler fiber, wherein the mass ratio of the second density filler to the high-performance fiber is 5:1.

[0073] Step 4: Preparation of base paper

[0074] 40% of cellulose fiber loaded with calcium sulfate whiskers, 30% of first density filler fiber, 30% of second density filler fiber, 30% of carbon fiber, 5% of polyimide fiber, 20% of mineral fiber, and 10% of glass fiber are configured, and the paper is deflaked in a deflaker, and then formed in a papermaking equipment and dried at 100°C. The final weight of the paper is 400g / m 2 .

[0075] Step 5: Preparation of pre-cured base paper

[0076] The dried base paper is immersed in a cashew nut shell oil modified phenolic resin solution to make the glue content of the paper 40%. After the immersion is completed, the paper is pre-cured at 100°C.

[0077] Step 6: Preparation of Friction Material

[0078] After pre-curing, the paper was hot pressed at 195°C and 6MPa to obtain the friction material, the properties of which are shown in Table 1.

[0079] Example 3

[0080] The load fibers used in this embodiment are cellulose fibers loaded with calcium sulfate whiskers, first density filler fibers and second density filler fibers, the pore regulating fibers are carbon fibers, polyimide fibers, mineral fibers and glass fibers, the concentration of the dihydrated calcium sulfate aqueous solution is 8%, the cellulose fibers are wood fibers, the regulator is sodium chloride, the sheath-core fibers are sheath-core fibers with polyester as the core layer, the first density fillers are barium sulfate, metal powder, graphite, aluminum oxide and magnesium oxide, the second density fillers are diatomaceous earth, nitrile rubber powder and phenolic resin powder, the high-performance fibers are aramid fibers, and the binder is a silicone-modified phenolic resin solution.

[0081] Step 1: Preparation of cellulose fibers loaded with calcium sulfate whiskers

[0082] Prepare 8% dihydrate and calcium sulfate aqueous solution, add wood fiber to vacuum negative pressure impregnation and stirring, add sodium chloride, mix evenly and react in a hydrothermal reactor for 150 minutes at a heating temperature of 120°C, wherein the mass ratio of dihydrate and calcium sulfate, cellulose fiber and sodium chloride in the dihydrate and calcium sulfate aqueous solution is 100:100:1.

[0083] Step 2: Preparation of first density filler fiber

[0084] 10% barium sulfate, 15% metal powder, 40% graphite, 10% aluminum oxide and 25% magnesium oxide were mixed evenly, added to the core-skin fiber with polyester as the core layer, stirred and heated to 120°C for 8 minutes. After stirring, excess filler was filtered out with a sieve to obtain a first density filler fiber, wherein the mass ratio of the first density filler to the core-skin fiber was 3:1.

[0085] Step 3: Preparation of Second Density Filler Fiber

[0086] Mix 2 times of diatomaceous earth, 0.5 times of nitrile rubber powder and 0.5 times of phenolic resin powder evenly, add to the high-performance fiber, stir and heat to 130°C, stir for 8 minutes, filter out excess filler with a sieve after stirring to obtain the second density filler fiber, wherein the mass ratio of the second density filler to the high-performance fiber is 3:1.

[0087] Step 4: Preparation of base paper

[0088] 30% of cellulose fiber loaded with calcium sulfate whiskers, 17% of first density filler fiber, 20% of second density filler fiber, 15% of carbon fiber, 3% of polyimide fiber, 10% of mineral fiber, and 3% of glass fiber are configured, and the paper is deflaked in a deflaker, and then formed in a papermaking equipment and dried at 100°C. The final weight of the paper is 400g / m 2 .

[0089] Step 5: Preparation of pre-cured base paper

[0090] The dried base paper is immersed in a cashew nut shell oil modified phenolic resin solution to make the glue content of the paper 30%. After the immersion is completed, the paper is pre-cured at 80°C.

[0091] Step 6: Preparation of Friction Material

[0092] After pre-curing, the paper was hot pressed at 180°C and 5MPa to obtain the friction material, the properties of which are shown in Table 1.

[0093] Comparative Example 1

[0094] Step 1: Preparation of base paper

[0095] 25 parts of diatomaceous earth, 20 parts of graphite, 2 parts of alumina, 3 parts of magnesium oxide, 20 parts of hemp fiber, 10 parts of aramid pulp, 10 parts of carbon fiber, and 10 parts of ES fiber are added to water at a concentration of 0.1%-1%, mixed and dispersed evenly, and formed in a papermaking equipment after dispersion is completed, and dried at 100°C. The final basis weight of the paper is 400g / m 2 .

[0096] Step 2: Preparation of pre-cured base paper

[0097] The dried base paper is immersed in a melamine-modified phenolic resin solution to make the glue content of the paper 20%. After the immersion is completed, the base paper is pre-cured at 60°C.

[0098] Step 3: Preparation of Friction Material

[0099] After pre-curing, the paper was hot pressed at 170°C and 1 MPa to obtain the friction material, the properties of which are shown in Table 1.

[0100] The friction performance provided by the embodiments of the present disclosure is tested in accordance with GB / T 35472.6 Test Method for Friction Elements of Wet Automatic Transmissions;

[0101] The calculation method of loss rate is: loss rate = (total mass of fiber filler - mass of base paper after drying) / total mass of fiber filler;

[0102] The porosity was tested by the liquid displacement method.

[0103] Table 1 Friction material properties

[0104] Dynamic friction coefficient Static friction coefficient Churn rate (%) Porosity (%) Example 1 0.14-0.16 0.18-0.20 5.3 68 Example 2 0.15-0.17 0.19-0.21 4.7 62 Example 3 0.15-0.17 0.19-0.21 5.8 65 Comparative Example 1 0.08-0.11 0.12-0.14 29 21

[0105] According to Table 1, the dynamic friction coefficient and static friction coefficient of the friction material of Examples 1-3 of the present disclosure are significantly higher than those of the comparative example, and the variation range is small. It can be seen that the friction material prepared by the raw materials and the method for preparing the friction material of the present disclosure has better friction performance. At the same time, the loss rate of the filler of Examples 1-3 of the present disclosure is small. It can be seen that in the process of preparing the friction material by the raw materials and the method for preparing the friction material of the present disclosure, since no filler is added in the process of preparing the base paper, the contamination of the filler to the mesh cloth is reduced and the problem of the difficulty of white water circulation is solved. The porosity of the friction material prepared by Examples 1-3 of the present disclosure is large. It can be seen that when the friction material prepared by the raw materials and the method for preparing the friction material of the present disclosure is used in oil, the friction material can retain more oil, thereby enhancing the cooling effect and improving heat resistance.

[0106] In summary, the friction material prepared by the method for preparing the friction material provided in the embodiment of the present disclosure has excellent friction performance, while avoiding the problem of mesh contamination and the problem of a large amount of filler remaining in the white water that is difficult to recycle, thereby reducing costs and being more environmentally friendly.

[0107] The embodiments of the present disclosure are described above. However, these embodiments are for illustrative purposes only and are not intended to limit the scope of the present disclosure. The scope of the present disclosure is defined by the appended claims and their equivalents. Without departing from the scope of the present disclosure, a person skilled in the art may make a variety of substitutions and modifications, which should all fall within the scope of the present disclosure.

Claims

1. A friction material, characterized in that: The friction material comprises: at least one load fiber, at least one pore adjustment fiber and a binder, each of the load fibers comprises a fiber matrix and a filler loaded on the fiber matrix, and a density difference between every two of the load fibers is less than a preset density difference.

2. The friction material according to claim 1, characterized in that: The mass ratio of the load fiber to the pore regulating fiber is (40-100):(31-65).

3. The friction material according to claim 1, characterized in that: The plurality of loaded fibers include cellulose fibers loaded with calcium sulfate whiskers, first density filler fibers, and second density filler fibers.

4. The friction material according to claim 3, characterized in that: The mass ratio of the cellulose fiber loaded with calcium sulfate whiskers, the first density filler fiber and the second density filler fiber is (20-40): (10-30): (10-30).

5. The friction material according to claim 3, characterized in that: The cellulose fiber loaded with calcium sulfate whiskers comprises a calcium sulfate dihydrate aqueous solution and cellulose fibers, wherein the concentration of the calcium sulfate dihydrate aqueous solution is 5%-10%; and / or, The first density filler fiber includes a first density filler and a sheath-core fiber, the second density filler fiber includes a second density filler and a high-performance fiber, and the density of the first density filler is greater than the density of the second density filler.

6. The friction material according to claim 5, characterized in that: The mass ratio of calcium sulfate dihydrate in the calcium sulfate dihydrate aqueous solution to the cellulose fibers is 1:1; and / or, The cellulose fibers include one or more of cotton fibers, hemp fibers and wood fibers; and / or, The mass ratio of the first density filler to the core-skin fiber is (2-5):1; and / or, The mass ratio of the second density filler to the high performance fiber is (0.5-5):1; and / or, The first density filler includes a density greater than 1.2 g / cm 3 of filler; and / or, The core-sheath fiber comprises one or both of a core-sheath fiber with polypropylene as the core layer and a core-sheath fiber with polyester as the core layer; and / or, The first density filler comprises one or more of barium sulfate, metal powder, graphite, aluminum oxide and magnesium oxide; and / or, The second density filler includes a density less than 1.2 g / cm 3 of filler; and / or, The high performance fiber comprises one or more of aramid fiber, ceramic fiber and carbon fiber; and / or, The second density filler includes one or more of diatomaceous earth, nitrile rubber powder and phenolic resin powder.

7. The friction material according to claim 1, characterized in that: The pore regulating fibers include one or more of carbon fibers, polyimide fibers, mineral fibers, and glass fibers.

8. A method for preparing a friction material, characterized in that: The preparation method of the friction material comprises: The load fibers and the pore-adjusting fibers are loosened and paper-made to obtain base paper; immersing the base paper in a binder to obtain a pre-cured base paper; The pre-cured base paper is subjected to a heat-pressing curing process to obtain a friction material.

9. The method for preparing the friction material according to claim 8, characterized in that: When the friction material is the friction material according to claim 5, the step of fluffinessing and papermaking the load fibers and the pore adjustment fibers to obtain the base paper comprises: adding cellulose fibers into a calcium sulfate dihydrate aqueous solution for immersion to obtain cellulose fibers pretreated with calcium sulfate whiskers; Under the first reaction condition, the pretreated cellulose fiber loaded with calcium sulfate whiskers and a conditioning agent are mixed to perform crystal growth to obtain cellulose fiber loaded with calcium sulfate whiskers; Under the second reaction condition, the first density filler and the sheath-core fiber are mixed and heated to obtain the first density filler fiber; Under the third reaction condition, the second density filler and the high performance fiber are mixed and heated to obtain the second density filler fiber; The cellulose fibers loaded with calcium sulfate whiskers, the first density filler fibers, the second density filler fibers and the pore regulating fibers are unraveled and paper-made to obtain base paper.

10. The method for preparing the friction material according to claim 9, characterized in that: The mass ratio of dihydrate and calcium sulfate in the dihydrate and calcium sulfate aqueous solution, the cellulose fiber and the conditioning agent is (20-100): (20-100): 1; and / or, The first reaction conditions include a crystal growth reaction time of 100 min-150 min and a reaction temperature of 100° C.-150° C.; and / or, The second reaction conditions include a stirring time of 5 min-10 min and a heating temperature of 105° C.-138° C.; and / or, The third reaction condition includes a stirring time of 5 min-10 min and a heating temperature of 120° C.-140° C.